Strategies for Strengthening Arabic Language Skills of Grade 6 Students of Madrasah Ibtidaiyyah - Yurianto, Ramdhan; Nadiroh, Nasikhotun; Hidayat, Arif; Nurunnisa, Amelia; Yusuf, Ari (Bilingua, 2024)
The ability to choose strategies is very necessary to achieve goals and education, especially for the selection of language skills learning strategies in elementary school students. One that can be used is a strategy to strengthen the language skills of elementary school students with a bilingual dormitory model. This study aims to examine what strategies are carried out by Madrasah Ibttidaiyyah Darul Hikmah Bantarsoka in strengthening the Arabic language skills of its students. This research is a descriptive qualitative research field. The research data came from observation, interviews and documentation. The results of this study show that the bilingual boarding program does not run easily, there are inhibiting and supporting factors. Inhibiting factors include the many complaints and demands of parents, the lack of time to learn Arabic, the students themselves. And the supporting factors are the support from the school, the use of gamification methods, the existence of dormitory assistants, and Arabic teaching teachers and the availability of supporting learning facilities such as Arabic hiwar modules, al-mufrodzat al-haitiyyah, Arabic flashcards, educational sound cards.